Prevalence and Morphological Variations of Prelacrimal Recess in Maxillary Sinus - A Retrospective CBCT Study - Anitha Palanisamy; Bakyalakshmi Karthikeyan; Benazir Najmutheen (Wolters Kluwer Medknow Publications, 2024)
Background: The pathology of the maxillary sinus (MS) can be treated using the prelacrimal recess approach, an intranasal method for accessing the MS. This approach exhibits significant individual variations in its prevalence and varying widths. Aim: To determine the occurrence of the prelacrimal recess (PLR) in the MS and explore its morphological variations. Methods: A retrospective analysis was performed on 225 cone beam computed tomography scans obtained from the department's archives. The patients ranged in age from 18 to 78. Statistical analysis were conducted to evaluate the frequency of PLR occurrence in the MS. Data from both sides were compared between males and females. Results: The analysis of the data revealed that PLR was present in 84.9% of patients with MS. Each patient exhibited asymmetry between the left and right sides. Although PLR was less likely to occur in women, the difference was not statistically significant. Conclusion: The anatomical variations of the PLR in individuals should be considered prior to procedures to prevent complications.